Relationship Between Inventory Management System and Company Performances - Pradhan, Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Inventory management system is software that helps hardware stores in companies, where store owners keep records of sales and acquisitions. Inventory management is a complex problem area for the management of the supply chain. In order to meet the customer demand, businesses need to have inventories to warehouses, while these inventories have holding costs which can be incurred by the frozen funds. The task of inventory management is, therefore, to determine the quantity of stocks that meets the demands, thereby preventing excess stocks. Inventory mismanagement means disappointed customers, excessive cash in warehouses and slower sales. This project removes the paperwork, human error, manual delay and the process is accelerated. Inventory Management Systems is an application designed for Windows operating systems that is based on the Inventory management area which produces the needed reports. Inventory Management Systems are able to track purchases and usable stock, tell a customer when it is time to reorder and how much to buy. Based on the inventory days and return of asset (ROA) analysis, the relationship between inventory management and company performance was estimated.